Factors affecting the growth of small and medium enterprise in Alor Setar, Kedah / Munirah Dziyauddin - Dziyauddin, Munirah (2013)
This research is about the factors affecting the growth of small and medium enterprise in Alor Setar, Kedah. SME is abbreviation of Small and Medium Enterprises. Malaysian SME can be grouped into three categories; micro, small, and medium. These groupings are decided upon based on either the number of people a business employs or the total sales or revenue generated by a business in a year. In Malaysia, SMEs play an important role in pushing the country towards continuous economic growth. The main objective of this research is to determine the factors that affecting the growth of SME in Alor Setar, Kedah. In this research, the researcher focused on the micro category. There have four independent variables that have been determined. The independent variables are innovation, financial, managerial function and marketing factor. All this independent variable is test with the dependent variable which is the growth of SME. This research use the primary data based on the questionnaire that had been distribute to the 50 entrepreneur in Alor Setar, Kedah. The methods that have been used in this research are descriptive statistics, hypothesis testing, reliability analysis, and multiple linear regression models. The researcher had found the factors that affecting the growth of SME in Alor Setar, Kedah are financial status and marketing.